THE EFFECTINES OF COMIC STRIPS AND TEXT IN TEACHING NARRATIVE TO IMPROVE STUDENTS’ READING COMPREHENSION - SITI RAHAYU (SECONDARY: Jurnal Inovasi Pendidikan Menengah, 2023)
This lesson is intended to investigate the effectiveness of using comic strips in improving students' reading comprehension in narrative texts. The learning analysis observed that the use of comics as a reading activity in the classroom was interesting and motivating for students. Besides that, in the journal the effects of comic strips used on reading comprehension of EFL students it was found that using comic strips led to high student performance. And to achieve the objectives of this research, a Quasi-Experimental research model is used. Data was collected from students of SMPN 41 grades 8A & 8B in Jakarta. Taking two classes, each consisting of 40 students and divided into experimental and control groups. Several tools such as pre-test, post-test are used to collect data. From the findings, it shows that the effectiveness of comic strips has succeeded in increasing students' reading comprehension as indicated by statistical scores in the post test of the experimental group (M = 73.56), SE (1.354), and the post test of the control group (ordinary) (M = 68.00 ), SE (1.506). At the end of the study, the Experiment Group made significant progress compared to the control group. ABSTRAKPembelajaran ini ditujukan untuk menginvestigasi keefektifan penggunaan potongan komik dalam meningkatkan pemahaman membaca siswa dalam teks Naratif. Analisis pembelajaran mengobservasi bahwa penggunaan komik sebagai activitas membaca di ruangan kelas menjadi menarik dan memotivasi siswa. Disamping itu, dalam jurnal efek potongan komik yang digunakan di pemahaman membaca dari siswa EFL ditemukan bahwa menggunakan potongan komik menjadikan tingginya performence siswa. Dan untuk mencapai tujuan penelitian ini, model penelitian Quasi-Experimental dipergunakan. Data dikumpulkan dari siswa SMPN 41 kelas 8A & 8B di Jakarta. Mengambil dua kelas yang masing – masing terdiri dari 40 siswa dan terbagi ke dalam kelompok eksperimen dan control. Beberapa alat seperti pre-test, post-test digunakan untuk mengkoleksi data. Dari temuan, ini menunjukkan bahwa keefektifan dari potongan komik sukses meningkatkan pemahaman membaca siswa sebagai indikasi oleh skor statisitik dalam post test dari kelompok ekperiment (M= 73.56), SE (1.354), dan post test dari kelompok control (biasa) (M=68.00), SE (1.506). Di akhir pembelajaran, Kelomok Experiment mengalami kemajuan secara signifikan dibanding kelompok komtrol.